АУЫЗЕКІ ҚЫТАЙ ТІЛІНДЕГІ ҚОЛДАНЫЛАТЫН КОНСТРУКЦИЯЛАР (Journal of Oriental Studies, 2016)
В статье рассматривается часто употребляемыеконструкций устной речи китайского языка.In this article it is considered often used construction oforal speech of the Chinese language.